The impact of loupes and microscopes on vision in endodontics. (19th August 2013) - Perrin, P.; Neuhaus, K. W.; Lussi, A.
Abstract Aim To report on an intraradicular visual test in a simulated clinical setting under different optical conditions. Methodology Miniaturized visual tests with E‐optotypes (bar distance from 0.01 to 0.05 mm) were fixed inside the root canal system of an extracted maxillary molar at different locations: at the orifice, a depth of 5 mm and the apex. The tooth was mounted in a phantom head for a simulated clinical setting. Unaided vision was compared with Galilean loupes (2.5× magnification) with integrated light source and an operating microscope (6× magnification). The influence of the dentists' age within two groups was evaluated: <40 years (n = 9) and ≥40 years (n = 15). Results Some younger dentists were able to identify the E‐optotypes at the orifice, but otherwise, natural vision did not reveal any measurable result. With Galilean loupes, the younger dentists <40 years could see a 0.05 mm structure at the root canal orifice, in contrast to the older group ≥40 years. Only the microscope allowed the observation of structures inside the root canal, independent of age. Conclusion Unaided vision and Galilean loupes with an integrated light source could not provide any measurable vision inside the root canal, but younger dentists <40 years could detect with Galilean loupes a canal orifice corresponding to the tip of the smallest endodontic instruments. Dentists over 40 years of age were dependent on the microscope to inspect the root canal system.